Crossing different ontological domains: the case of appena - Gradimondo, Valeria; Tovena, Lucia M. (Proceedings of the Amsterdam Colloquium, 2024)
This paper investigates the semantics of the Italian multi-faceted particle appena, which can be interpreted as an adverb (namely barely, only, just) and as a temporal connective (as soon as). We argue for the presence of the same underlying pattern for all its interpretations, and develop its formalisation in a (neo) Davidsonian event-based semantics.